PENGARUH QUIET QUITTING DAN WORK ENGAGEMENT TERHADAP KINERJA KARYAWAN DENGAN WORK-LIFE BALANCE SEBAGAI VARIABEL MEDIASI PADA PT POS INDONESIA KCU SEMARANG - Alfian Nur Hakim; Qristin Violinda; Farah Chalida Hanoum T (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the effects of Quiet Quitting and Work Engagement on Employee Performance with Work-Life Balance as a mediating variable at PT Pos Indonesia KCU Semarang. A quantitative approach was employed using a saturated sampling technique involving 88 employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 4. The results showed that Quiet Quitting and Work Engagement had positive and significant effects on Employee Performance. Work Engagement also had a positive and significant effect on Work-Life Balance, whereas Quiet Quitting and Work-Life Balance did not significantly affect their respective dependent variables. Furthermore, Work-Life Balance did not mediate the effect of Quiet Quitting on Employee Performance but successfully mediated the effect of Work Engagement on Employee Performance. The findings indicated that Work Engagement was the most dominant factor in improving Employee Performance.